2015
DOI: 10.1007/s00300-015-1715-y
|View full text |Cite
|
Sign up to set email alerts
|

Microplankton succession in a SW Greenland tidewater glacial fjord influenced by coastal inflows and run-off from the Greenland Ice Sheet

Abstract: Studies of annual successions and inter-annual variations in sub-Arctic and Arctic microplankton assemblages are required in order to understand the structure and function of marine ecosystems. This study depicts the microplankton ([20 lm) structure in a sub-Arctic tidewater glacial fjord system, SW Greenland. The descriptions are based on monthly net hauls collected between January 2006 and December 2010. Two blooms, with distinctive species compositions, were identified across all years: a spring bloom and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 35 publications
3
42
0
Order By: Relevance
“…Concurrent with the depletion of nutrients (DSi and nitrate) in the upper water layer, a shift in the species composition occurred and diatoms became less abundant (Figure ). The same temporal pattern is observed in the interannual phytoplankton succession at station GF3 (Figure ) which consistently shows a succession from diatoms to haptophytes in spring, coinciding with a decrease of DSi in surface water [ Juul‐Pedersen et al , ; Krawczyk et al , ] (Figure ). In summer, new nutrients are resupplied to the surface layer through subglacial freshwater discharge (Figure ).…”
Section: Resultssupporting
confidence: 66%
“…Concurrent with the depletion of nutrients (DSi and nitrate) in the upper water layer, a shift in the species composition occurred and diatoms became less abundant (Figure ). The same temporal pattern is observed in the interannual phytoplankton succession at station GF3 (Figure ) which consistently shows a succession from diatoms to haptophytes in spring, coinciding with a decrease of DSi in surface water [ Juul‐Pedersen et al , ; Krawczyk et al , ] (Figure ). In summer, new nutrients are resupplied to the surface layer through subglacial freshwater discharge (Figure ).…”
Section: Resultssupporting
confidence: 66%
“…Dinobryon balticum) and the diatom Melosira arctica characterised the inner fjord waters along with the lowest recorded salinity. D. balticum is regarded as preferring low-saline summer surface waters in sub-Arctic and Arctic fjords (Hasle & Heimdal 1998, Krawczyk et al 2015. M. arctica was recorded only in inner Young Sound throughout the study and is commonly found attached to sea ice or in the plankton under or in the vicinity of ice (Hasle & Syvertsen 1996).…”
Section: Fjord Watersmentioning
confidence: 99%
“…Strong freshwater input delivers loads of silt, carrying Si(OH) 4 to the surface waters of the inner fjord. Generally, diatoms and colonial chrysophytes are common components of sub-Arctic and Arctic summer waters (Hasle & Heimdal 1998, Okolodkov et al 2000, Krawczyk et al 2015. The low-salinity but warmer waters re corded in mid Young Sound indicate summer heating of the fresher surface waters as these waters are transported out of the fjord.…”
Section: Fjord Watersmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature and salinity gradients along the fjords are regulated by the fjords' seasonal circulation systems and their various physical drivers (Mortensen et al, , ). Besides being important components for melting of the Greenland Ice Sheet (GIS) and associated global sea level rise, these seasonal circulation systems determine biological parameters: changes in fjord circulation and physical drivers seem to explain spatial gradients in metazooplankton communities (Arendt et al, ; Tang et al, ) and seasonal variations in phytoplankton species composition and primary production (Juul‐Pedersen et al, ; Krawczyk et al, ; Meire et al, ). Biogeochemical gradients generated by these circulation systems also influence the exchange of properties between fjords and the open ocean: Rysgaard et al () found that the mixing of surface water inside the fjord with coastal water masses regulated the air‐sea gas exchange of CO 2 in Godthåbsfjord during summer.…”
Section: Introductionmentioning
confidence: 99%